2009
DOI: 10.4103/0971-4065.53324
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associations of hepatitis C viremia in hemodialysis patients at a tertiary care hospital

Abstract: Hepatitis C virus (HCV) infection in hemodialysis (HD) is a significant problem. We evaluated the prevalence and associations of HCV viremia in our HD patients. All patients undergoing maintenance HD at our center were tested for HCV RNA by PCR after written informed consent. Detailed history regarding age, sex, and duration of dialysis, frequency of dialysis, blood transfusions in one year, number of dialysis centers, dialyzer reuse/fresh use, and recent laboratory data was recorded. A total of 119 patients (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
34
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 31 publications
6
34
1
1
Order By: Relevance
“…17,18 In our study, anti-HCV antibodies were found in 30.5% of patients at the end of 18 months of our study period, which is lower than studies conducted by Chandra et al (46%) 19 but was higher than studies conducted by Jain (29%) 20 and Jasuja (22%). 21 Our hospital is a tertiary care center where many patients are referred for HD from other HD centers of Uttarakhand and patients registered at our center did take HD at other centers as per their convenience. Out of 17 patients seroconverting for anti-HCV antibodies, 10 gave history of receiving HD at some other dialysis center.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 In our study, anti-HCV antibodies were found in 30.5% of patients at the end of 18 months of our study period, which is lower than studies conducted by Chandra et al (46%) 19 but was higher than studies conducted by Jain (29%) 20 and Jasuja (22%). 21 Our hospital is a tertiary care center where many patients are referred for HD from other HD centers of Uttarakhand and patients registered at our center did take HD at other centers as per their convenience. Out of 17 patients seroconverting for anti-HCV antibodies, 10 gave history of receiving HD at some other dialysis center.…”
Section: Discussionmentioning
confidence: 99%
“…15 In a study from New Delhi, 119 patients undergoing HD were enrolled and the prevalence of HCV RNA positivity was found to be as high as 27.7%. 16 The prevalence of HCV infection in renal transplant recipients in India has been reported to be as high as 26.2-55.9%. 17 The prevalence of HCV infection in HCWs has ranged from 0% to 4%, and is notably higher among staff working in HD units.…”
Section: Prevalence Of Hcv In Indiamentioning
confidence: 99%
“…The prevalence of HCV infection in patients undergoing dialysis is persistently greater than that in the general population being endemic in haemodialysis (HD) units around the world, predominantly in Mediterranean and developing countries of the Middle and Far East. Nosocomial transmission of HCV infection has been reported to be a considerable route in modern hospital dialysis units, particularly during the outbreaks of infection [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%